EKSISTENSI QAUL AL-SHAHABI SEBAGAI DALIL SYAR’I - Abdul Hakim (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
The source of Islamic law is the main foundation a mujtahid for exploring Islamic law for existing arguments, both agreed ptopositions or disputed. Qaul Shahabi is one of the syar’i arguments wich became a discussion of scholars about the success in the determination of the law. Study of Qaul Shahabi become one of the interesting themes among experts ushul fiqh, even though they put it in the position of the disputed argument. However, the majority of scholars use Qaul Shahabi as a backrest in deciding the case of islamic law, especially events that are not partially explained in the Alquran and Hadis. Debate among these scholars only limited to which friends can be used as a basis and reference, but that does not prevent them from making Qaul Shahabiy a shar'i proposition